2021
DOI: 10.1149/2162-8777/ac1a0b
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Ge-on-Nothing and Epitaxial Ge on Si-on-Nothing as Virtual Substrates for 3D Device Stacking Technologies

Abstract: Two new templates for strain-relaxed detachable Ge are introduced. The first one is based on epitaxial growth of Ge on a Si-on-Nothing (SiON) platform while the second consists of Ge-on-Nothing (GeON). The SiON and GeON templates are obtained from the reorganization of macro-porous Si and Ge, respectively, fabricated on regular Si substrates using conventional lithography, dryetching and annealing routines. Both templates contain similar densities of threading dislocations as typically obtained for conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…An in-house fabricated epitaxially grown Ge virtual substrate (VS) [11] was used to optimize the ECCI measurement routine. The thickness of the Ge VS layer is ~1 μm and the expected TDD is ~2-5e7 cm -2 [11][12]. This TDD is significantly higher compared to the TDD of the Si1-xGex SRBs.…”
Section: Methodsmentioning
confidence: 99%
“…An in-house fabricated epitaxially grown Ge virtual substrate (VS) [11] was used to optimize the ECCI measurement routine. The thickness of the Ge VS layer is ~1 μm and the expected TDD is ~2-5e7 cm -2 [11][12]. This TDD is significantly higher compared to the TDD of the Si1-xGex SRBs.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, two labs have reported the successful fabrication of a Ge-on-Nothing (GeON) structure based on the reorganization of macro-porous Ge at high temperatures. 39,40) This method is based on the Si-on-Nothing fabrication suggested by Mizushima et al 41) The GeON fundamental fabrication procedure is shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%